Answer:
x = -8
y = 9
Step-by-step explanation:
to solve this expression using simultaneous equation, we would say let
y =9............................................. equation 1
6x + 5y =-3............................................equation 2
substitute equation 1 into equation 2
-3 = 6x + 5y............................................equation 2
6x + 5(9) = -3
6x + 45 = -3
collect the like terms
6x = -3-45
6x = -48
divide both sides by the coefficient of x which is 6
6x/6 = -48/6
x = -8
therefore y = 9
x = -8
Answer:
What is it you need help with?
Step-by-step explanation:
Which one
Answer:
1
Step-by-step explanation:
G(-1) = -1+3
= 2
F(2) = 5(2) - 10
= 0